Low prevalence of human papillomavirus in oral cavity squamous cell carcinoma in Queensland, Australia. Issue 9 (18th April 2016) - Emmett, Sarah; Jenkins, Glenn; Boros, Samuel; Whiteman, David C.; Panizza, Benedict; Antonsson, Annika
Abstract : Background: While human papillomavirus (HPV) is an accepted risk factor for oropharyngeal squamous cell carcinoma (SCC), its aetiological role in oral cavity SCC remains unclear. This study aimed to determine the HPV prevalence in an Australian population. Methods: DNA was extracted from 63 formalin‐fixed paraffin‐embedded tumour specimens histologically confirmed as SCC of the oral cavity, diagnosed during 2006–2012. Clinical data were extracted from medical records. HPV presence was determined by polymerase chain reaction. Positive samples were typed by sequencing. Immunohistochemistry was used to assess p16 INK4A, p53, pRB, Ki67, Cyclin D1 and p21 WAF1 expression. Results: Five of the 63 tumours (8%) were positive for HPV DNA (three HPV‐16 positive and two HPV‐18 positive). Two tumours overexpressed p16 INK4A (3%) and one of these was also HPV positive. Overexpression of Cyclin D1 correlated significantly with tumour recurrence ( P = 0.029) and death ( P = 0.002). Conclusions: This study has identified a low prevalence of high‐risk HPV in Queensland, Australia.